An Experiment of Verification of Multi-agent Robotic Soccer Plans with Model Checking - S., Rui C. Botelho A.; Andrade, Aline M. S.; Costa, Augusto Loureiro da; Barboza, Frederico J. R. (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC); 2013: Anais do VII Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações, 2013)
In this paper we present an experiment of model checking which consists of the verification of plans of a multi-agent system for simulated robot soccer. This system is of considerable complexity because it is concurrent, nondeterministic and with partial vision of the environment. Some solutions adopted relative to modeling and process of verification to circumvent state space explosion are reported.